Improving Reading Comprehension on Descriptive Text Through STAD for the First Year Students - Wiratno Wiratno; Dessy Ayu Ardini (Journal of Development Research, 2022)
The purposes of this research tries to know :1) How is the process of teaching Descriptive Text through STAD method for the first year junior high students, 2) How can STAD improve reading comprehension on Descriptive Text for the first year junior high students. The results of the research show that STAD is an effective method to teach reading. This method made the students was more active in following teaching and learning process with could understand the material. After the researchers applied SQ5R technique and gave the post test, it is found that mean score increased from 67.18% to 75 %. It can be concluded that the hypothesis is accepted, or on the other words STAD technique can improve reading comprehension the students’ English achievement on Descriptive text.